The Effect of Selected Minimum and Conventional Tillage Practices in Vineyard Cultivation on Vine Performance - Van Huyssteen, L.; Weber, H. W. (South African Journal of Enology and Viticulture, 2017)
A long-term vineyard cultivation experiment, comprising six tillage treatments which represent a "conventional'' cultivation group as well as a group of "minimum" tillage practices, was started in 1968 at Nietvoorbij Experimental Farm of the OVRI, Stellenbosch. The first group included (i) the "shallow trench furrow", (ii) the "deep trench furrow", and (iii) the locally customary "clean cultivation" systems, and the second group comprised (i) a straw mulch cover on the soil surface, (ii) chemical weed elimination by herbicides, and (iii) a permanent "sward" of indigenous weeds. Distinct differences in vine performance between treatments were found. The general appearance, nutritional status and some important growth parameters of vines, as well as yield and quality of grapes, musts and wines from the straw mulch and herbicide treated (minimum) plots were markedly superior to the same properties of vines, grapes and wines from the conventionally tilled plots and the sward treatment, the latter due to competition of weeds for water and nutrients. However, a tentative economical analysis showed that the deep furrow trenching gave a sufficiently high yield to merit further consideration, although it could not reach the economical performance of the herbicide treatment.